Policy Games with Liquidity Constrained Consumers - Alice Albonico; Lorenza Rossi (Università degli Studi di Pavia, Dipartimento di Economia Politica e Metodi Quantitativi (EPMQ), 2011)
In the light of the recent financial crisis, we investigate the effects generated by limited asset market participation on optimal monetary and fiscal policy, where monetary and fiscal authority are independent and play strategically. We find that limited asset market participation strongly affects the optimal steady state and the optimal dynamics of the different policy regimes considered. In particular: (i) both in the long run and in short run equilibrium, a greater inflation bias is optimal than in the standard representative agent economy; (ii) in response to a markup shock, fiscal policy becomes more active as the fraction of liquidity constrained agents increases; (iii) optimal discretionary policies imply welfare losses for Ricardian, while liquidity constrained consumers experience welfare gains with respect to Ramsey.
Keywords: E3; E5; 330; liquidity constrained consumers; optimal monetary and fiscal policy; strategic interaction; inflation bias